Vitamin D status in Bangladeshi subjects: a laboratory based study - Islam, AKM Monwarul; Hasan, Md Nayeemul; Rahman, Kazi Mizanur; Asaduzzaman, Md; Rahim, Muhammad Abdur; Zaman, Shahana; Islam, Md Rashedul; Jesmin, Humayra; Yeasmin, Lovely (BIRDEM Medical Journal, 2019)
Background: Vitamin D plays important role in normal functioning of multiple organs of the body. Hypovitaminosis D is known to be prevalent worldwide including the tropical countries. The present study was carried out to evaluate the vitamin D status in Bangladeshi patients undergoing laboratory investigation for vitamin D. Methods: This was a laboratory-based study. Data were extracted from the database of a diagnostic centre of Dhaka city and were analysed. Vitamin D status was defined as follows: deficiency 0 to <20 ng/ml, insufficiency 20 to <30 ng/ml, sufficiency 30-100 ng/ml and potential toxicity >100 ng/ml. Results: A total of 793 plasma vitamin D level reports were analysed. Out of 793 subjects, 269 (33.9%) were male and 524 (66.1%) were female. Majority (62.0%) were between 21 and 60 years of age. Mean (+/- standard deviation) vitamin D level of the study subjects was 21.66 (+/- 18.63) ng/ml. Eighty-six percent had hypovitaminosis D; 61.4% had deficiency and 24.1% had insufficiency. Vitamin D level was found sufficient in 13.1% subjects. Among the deficient subjects, 31.6% were male and 68.4% were female; among the insufficient subjects, 35.1% were male and 64.9% were female. Sixty-eight percent of the deficient subjects belonged to the 21 to 60 year age group, whereas 57.1% of the insufficient subjects were between 21 and 60 years. Conclusion: Hypovitaminosis D is common among the real-world clinical subjects undergoing vitamin D estimation in Bangladesh. Middle-aged females are more likely to be affected Birdem Med J 2019; 9(3): 202-206